Double stranded-RNA-mediated activation of P21 gene induced apoptosis and cell cycle arrest in renal cell carcinoma - Whitson, Jared M (2009)
Small double stranded RNAs (dsRNA) are a new class of molecules which regulate gene expression. Accumulating data suggest that some dsRNA can function as tumor suppressors. Here we report further evidence on the potential of dsRNA mediated p21 induction. Using the human renal cell carcinoma cell line A498, we found that dsRNA targeting the p21 promoter significantly induced the expression of p21 mRNA and protein levels. As a result, dsP21 transfected cells had a significant decrease in cell viability with a concomitant G1 arrest. We also observed a significant increase in apoptosis. These findings were associated with a significant decrease in survivin mRNA and protein levels. This is the first report that demonstrates dsRNA mediated gene activation in renal cell carcinoma and suggests that forced over-expression of p21 may lead to an increase in apoptosis through a survivin dependent mechanism.